2010
DOI: 10.1007/s11255-010-9752-5
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic versus open hydrocelectomy for the treatment of adult hydroceles: a randomized controlled clinical trial

Abstract: Endoscopic method is a viable option in the treatment of hydrocele. Outstanding feature of the endoscopic method is an earlier achievement of a better cosmetic outcome and a comfortable postoperative period when compared with the conventional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
1
0
4
Order By: Relevance
“…Bin et al concluded that “the combination of minimal hydrocelectomy and scrotoscopy seems to be an encouraging technique ( 1 )”. This result can support the previous observation that minimally invasive hydrocelectomy is safe and requires a short operative time ( 2 ). It is agreeable that the technique can be useful but the case selection is the important prerequisite.…”
supporting
confidence: 91%
“…Bin et al concluded that “the combination of minimal hydrocelectomy and scrotoscopy seems to be an encouraging technique ( 1 )”. This result can support the previous observation that minimally invasive hydrocelectomy is safe and requires a short operative time ( 2 ). It is agreeable that the technique can be useful but the case selection is the important prerequisite.…”
supporting
confidence: 91%
“…In another endoscopic hydrocelectomy study by Emir et al . 18 , the authors reported a recurrence rate of 7.4% (2/27). They used a 27 F resectoscope with a 30-degree lens for scrotoscopy and a cylindrical electrode.…”
Section: Discussionmentioning
confidence: 97%
“…Es wird angenommen, dass es durch die große Schnittfläche sowie durch die Dissektion der Hydrozelenwand von der Tunica dartos häufiger zu Nachblutungen, Hämatomen und weiteren Komplikationen kommt [12]. Als weitere Therapiemöglichkeiten wurden die minimalinvasiven Methoden wie die Hydrozelenaspiration mit Sklerosierung sowie die laparoskopische Hydrozelenresektion untersucht [13,14]. Hierbei zeigten sich vergleichbare Komplikationsraten, jedoch mit höheren Rezidivraten in bis zu 11% [13].…”
Section: Diskussionunclassified
“…Komplikationen konnten demnach nur festgestellt werden, wenn sich die Patienten im Verlauf wieder im Krankenhaus vorstellten [2,4,5]. Des Weiteren wurde in einigen Studien standardisiert eine antibiotische Prophylaxe eingesetzt [2,14,15,16]. Hier zeigten sich postoperativ Infektionsraten von bis zu 5%.…”
Section: Diskussionunclassified
See 1 more Smart Citation